Novel mutation in MASP1 gene in a new family with 3MC syndrome - Basdemirci, Muserref; Sen, Askin; Ceylaner, Serdar (Lippincott Williams & Wilkins, 2019)
[Abstract Not Available]
Keywords: Malpuech-Syndrome; Defect